2006
DOI: 10.1159/000096211
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal Development of Entorhinodentate Projection of the <i>Reeler</i> Mutant Mouse

Abstract: We anterogradely labeled entorhinodentate axons by the injection of biotin dextran amine into the entorhinal cortex of adult wildtype and reeler mice to clarify whether the course and terminal endings of the reeler entorhinal projection are normal or not. We found that in the reeler mouse, biotin dextran amine-labeled entorhinodentate fibers arising from the entorhinal cortex curved around the hippocampal fissure instead of crossing it, whereas in the wildtype mouse, they crossed the fissure as a perforant pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 95 publications
(37 reference statements)
1
8
0
Order By: Relevance
“…SDF‐1 is, inter alia, produced by astrocytes, which are abundantly located at the HF. Concordant with previous studies, we observed astrogliosis in the vicinity of the HF in the reeler mouse (Muraoka et al, ; this study). The higher number of astrocytes in reeler mice may thus account for increased SDF‐1‐levels, causing enhanced chemoattractive signaling onto CR‐cells.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…SDF‐1 is, inter alia, produced by astrocytes, which are abundantly located at the HF. Concordant with previous studies, we observed astrogliosis in the vicinity of the HF in the reeler mouse (Muraoka et al, ; this study). The higher number of astrocytes in reeler mice may thus account for increased SDF‐1‐levels, causing enhanced chemoattractive signaling onto CR‐cells.…”
Section: Discussionsupporting
confidence: 93%
“…Thus, quantification of SDF‐1 immunoreactivity revealed a significantly higher SDF‐1 immunoreactivity in the reeler mice (Figure c3). Furthermore, using confocal microscopy, a higher number of GFAP‐positive cells and processes were observed in the reeler mice, suggesting that gliosis could have contributed to the observed phenotype (Muraoka, Katsuyama, Kikkawa, & Terashima, ; Supporting Information Figure S2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The perforant pathway is the major input to the hippocampal formation from the entorhinal cortex, and it crosses the hippocampal fissure to terminate in the hippocampus proper and the dentate gyrus (van Groen et al . 2003; Muraoka et al . 2007) (Fig.…”
Section: Morphological Alterations In the Central Nervous System Of Rmentioning
confidence: 99%
“…4F). Glial Fibrillary Acidic Protein (GFAP) immunostaining suggested that increased gliosis both in the reeler and SRK prevents penetration of the axons from the entorhinal cortex across the hippocampal fissure (Woodhams and Terashima 1999, 2000; Muraoka et al . 2007) (Fig.…”
Section: Morphological Alterations In the Central Nervous System Of Rmentioning
confidence: 99%